THE RELATION BETWEEN LEVEL KNOWLEDGE OF SMOKING ADOLESCENTS WITH BEHAVIOR SMOKING AT MADRASAH ALIYAH SAADAHTUDDARAIN MAMPANG SOUTH JAKARTA IN 2022 - Shafa’Afifah Tamimi; Istiqomah NA (Afiat, 2022)
Introduction Knowledge has a big role in influencing smoking behavior, especially in adolescents. Adolescents who have poor knowledge tend to have a greater risk of becoming smokers which will result in adolescents in the future becoming unhealthy adolescents. The purpose identify the relationship between the knowledge level of adolescent smokers and smoking behavior in MA Saadahtuddarain Mampang. The research methods used is descriptive correlation. Samples were taken using the total sampling technique as many as 35 respondents. Research analysis technique using univariate analysis and bivariate analysis using Chi-Square α=5%. The results showed that the level knowledge of adolescent smokers was good in the smoking behavior category mostly in light smoking behavior as much as 5 (14.3%), the knowledge level of adolescent smokers was quite good in the smoking behavior category mostly in heavy smoking behavior as much as 4 (11.4%) and the level knowledge of adolescents who are not good in the category of smoking behavior are mostly in heavy smoking behavior as much as 13 (37.1%). From the results of the analysis obtained a P Value of 0.009 this value < α=5%, then the hypothesis rejects H0. The conclusion is that there is a relationship between the knowledge level of adolescent smokers and smoking behavior in MA Saadahtuddarain Mampang. Suggestions for teachers to hold health seminars more often about the dangers of smoking.